Identification of causative mutation for the white coat phenotype in swamp buffalo. - CGIAR Research Program on Livestock (2020)
Journal article published - Genomic Analysis Revealed a Convergent Evolution of LINE-1 in Coat Color: A Case Study in Water Buffaloes (Bubalus bubalis).